Evolution and Issues in the Nursing Profession - CIISOQ, CIISOQ (Operating Room Nurses Association of Canada Journal, 2019)
A nurse for more than forty years, Monique Trachy gives us a picture of what it is to be an operating room nurse and sheds light on the major issues facing this profession, at the core of what is happening in the health sector.